Entropy generation in Johnson-Segalman peristaltic flow with magnetic field and activation energy - Zahir, Hina; Akram, Javaria; Bayram, Mustafa; Shakeel, Mehnaz; Fatima, Rabbia; Rezapour, Shahram; İnç, Mustafa (Wiley-V C H Verlag Gmbh, 2024)
This study examines entropy generation in the peristaltic flow of Johnson-Segalman fluid through a curved channel, considering the effects of Hall and ion slip due to an externally applied magnetic field and activation energy. The fluid dynamics are modeled using a highly nonlinear mathematical framework, which is non-dimensionalized and simplified with a lubrication approach. Numerical solutions are obtained using the shooting technique to analyze fluid flow properties. The results, presented graphically, provide a comprehensive understanding of the interactions between the non-Newtonian characteristics of the Johnson-Segalman fluid, entropy generation, and activation energy effects. The study finds that increasing the Hall parameter enhances entropy generation. Higher activation energy increases the rate of chemical reactions and by-products, raising system randomness. Additionally, reducing the channel curvature or increasing the curvature parameter elevates the system's entropy. These insights are valuable for biomedical and industrial applications.
Keywords: Asymmetric Channel